Information System Security Audit SIMKA(Sistem Informasi Kearsipan) at Badan Pendapatan Daerah Jawa Barat Kota Bandung III Using COBIT 5 Framework and Standard IS0/IEC 27002 - Suci Fitriani Setiawan; Titan Parama Yoga; Budiman Budiman (Research Collaboration Community (RCC), 2023)
One of the main problems for an agency or a company is the security of information systems. High security is needed to maintain the confidentiality and misuse of information within the organization. To improve the security of business operations and the quality of information technology resources, it is necessary to evaluate to op Badan Pendapatan Daerah Jawa Barat Kota Bandung III, namely SIMKA BAPENDA whose function is to collect data on PKB (pajak kendaraan bermotor) and BBNKB (bea balik nama kendaraan bermotor) which manage the data computerized. The purpose of this study is to carry out a security audit of SIMKA BAPENDA at the Badan Pendapatan Daerah Jawa Barat Kota Bandung III using the COBIT 5 framework and ISO/IEC 27002 to document audit findings of the information system audit of the Badan Pendapatan Daerah Jawa Barat Kota Bandung III to make a report on the audit results. Based on the results of research that has been done through interviews and questionnaires using framework and using the APO13 and DSS05 sub domains, the results show that the Capability Existing is at level 1 while Capability Level is level 3 so the Capability Gap is 2.